Controls on generation and accumulation of blended gases (CH4/H2/He) in the Neoproterozoic Amadeus Basin, Australia. (June 2022) - Leila, Mahmoud; Loiseau, Keanu; Moretti, Isabelle
Abstract: Various gases are generated in the subsurface, by diagenetic processes, fluid/rock interactions, maturation of petroleum source rocks and microbial activity. Often these gases just leak at the surface but sometimes they may accumulate in a subsurface trap. The present study investigates the case of the southern part of the Amadeus Basin, Australia, where exploration wells tested a blend of hydrocarbon (HC), helium (He) and hydrogen (H2 ). In Mt Kitty-1 well, He- and H2 -rich gases were reported (He ∼9%, H2 ∼11.4%) with traces of HC, whereas C1 and C2+ HC gases associated with He were discovered in Magee-1 well. Seismic and well data elucidate accumulation of the gas blend within a classical subsurface system with a structural trap, a permeable reservoir and a thick salt layer as seal. This salt, the Proterozoic Upper Gillen, is overlying the Heavitree sandstones and fractured basement reservoirs. The former is dominated by intergranular porosity (∼13%), whereas the latter is commonly associated with complex patterns of fractures associated with deep-seated faults. The sources of blended gases are different: thermal cracking of organic matter for hydrocarbons, radiolytic decay of radioelements for helium. Radiolysis, and water reduction as well as oxidation of hydrocarbons are open hypothesizes for H2 generation in the study region. Neoproterozoic and Early Paleozoic tectonic episodes (e.g. Petermann; Alice Springs) allowed the formation of various structural traps where the gas blend was accumulated. The large quantity of He, light gas slowly generated by the crustal radioactivity indicates that the seal is very efficient and that accumulations could have been in place for millions of years very likely with an evolving CH4 /H2 /He ratios through time. The presence of gas chimneys and surface depressions in the basin indicate that the generation, and/or migration of the gases are still active. All the data are consistent with a long-term accumulation of this gas blend, different from the short term H2 retention in the reservoir that was proposed in other contexts such as in Mali. Highlights: Unusual CH4 /H2 /He gas blend was discovered in the Amadeus Basin, Australia. Hydrocarbon gases are wet and have thermogenic origin. Natural H2 and He were generated by radioactive decay of U and Th. Proterozoic salt layers are effective seal for the gas blend. Circular depressions and gas seeps occur where the salt is thin.